(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Numerous research studies have been carried out to explore the effectiveness of incorporating virtual reality in education and training. This article highlights some of these studies and examines the rationale behind using virtual reality. The article discusses the pros and cons of using virtual reality and proposes guidelines for when to utilize it and when not to.